POTENSI EKOWISATA DIKAWASAN TAMAN HUTAN RAYA (TAHURA) NIPA-NIPA DIKELURAHAN WATU-WATU - Isanto, Isanto (Jurnal Penelitian Pendidikan Geografi, 2018)
This research aims to know the Potential of Ecotourism in Tahura Nipa-Nipa Area in Watu-Watu Village. The type of this research is descriptive qualitative research. The aim is to get an overview of the ecotourism potential that is found in Kawasa Taman Hutan Raya (TAHURA) Nipa-Nipa. To get information from the researcher using the key informants. The informants in this research are determined based on the research needs. Data collection techniques used are through interviews, observation and documentation. Data obtained from 6 informants namely the Department of Tourism as much as 1 person, the Forest Service in this case Unit PelaksaTeknis Daerah (UPTD) as much as 1 person and the Community who live around Tahura Nipa-Nipa in Kelurahan Watu-Watu as many as 4 people. Based on the result of the research from the interview of the informant, the result of research is the Potential of Ecotourism in Tahura Nipa-Nipa Area in Watu-Watu Village in the form of Flora potency in the form of Ironwood, Bolo-bolo and others. For the type of fauna that exist in the form of monkey macaca endangered animals Sulawesi, some species of dragonflies and monitor lizards, in addition there are other promising ecotourism potential of natural attractions such as waterfalls, camping places. In the study there is also another potential in the area of Tahura Nipa-Nipa ie there is agricultural land managed by surrounding communities who are familiar with the farmers Subur Makmur